Diversi Sebagai Bentuk Penyelesaian Perkara Pidana Anak dalam Sistem Peradilan Pidana Anak - Mahka, Muh Fachrur Razy; Karman Jaya; Mirfan; Asriyani Ismail (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin Makassar, 2023)
This research describes the concept of diversion in Indonesia's children criminal justice system, with a focus on its implementation and the factors that encourage children to become involved in criminal offenses. The concept of family as the basic unit of society is considered, and children are regarded as a trust that requires protection and loving care. Diversion, as a transfer of the settlement of children's cases from the criminal justice process to out of court, supports a rehabilitative and coaching approach This research uses Kuliatatif research by analyzing the data obtained from the research results, both from primary and secondary data Collecting data and information related to the object of this research, the author conducted research at the Gowa Police Office, South Sulawesi. The results showed that 55% of respondents supported the diversion approach, indicating a paradigm shift in the handling of children in conflict with the law. In addition, the study identified factors that encourage children to commit criminal offenses, including the role of family, environment, and social policy. The findings indicate the need for preventive approaches and appropriate interventions to avoid children engaging in dangerous and harmful behaviors. The results of this study provide insights for juvenile justice institutions and related parties in optimizing diversion as a more humane and effective way of dealing with children involved in criminal acts.